(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
The irrigation infrastructures in Farmer’s Managed Irrigation Systems (FMIS) of Nepal were mostly built from the local materials of mud, stone, and forest products with rudimentary traditional methods, practiced over many centuries. These systems are operated and maintained solely by the community farmers or an individual family. The Nepal Irrigation Sector Project (NISP), funded under the credit assistances of the World Bank, sponsored the modernization of these FMIS in the three western regions of Nepal from 1998 to 2004. The paper gives an account of the infrastructures built under the project to modernize the FMIS, and presents some facts about the impacts of the assistances to FMIS in relieving problems faced by farmers. The structures in the FMIS differ nominally according to the ecological region, due to the terrain and characteristics of the conveyance systems. In the hills, generally, lining and cross drainage structures are common; whereas, in the Terai, it is mostly the headworks structure due to lack of traditional materials as shrubs and forest products. The NISP assisted these FMIS with the participation of the users and their contribution in the civil works from seven to 15 percent. The users were involved in the design and construction of the infrastructures from the very initiation of the schemes. The project had good impacts on system performance and, thus, in agriculture production. Key words: FMIS; Irrigation; Participatory development; Water distribution; Modernization; Nepal DOI: 10.3126/hn.v6i0.4196 Hydro Nepal Journal of Water, Energy and Environment Vol. 6, January 2010 Page: 55-60 Uploaded Date: 24 January, 2011